Changes in Retinal Nerve Fiber Layer and Macular Ganglion Cell-Inner Plexiform Layer Thickness after Spinal Surgery in the Prone Position - Thoranis Deeprasertwit; Piya-Orn Bunyaprateeprat; Niphon Chirapapaisan; Sirichai Wilartratsami; Pratuangsri Chonphimai; Nuchanat Ritthison; Yanee Mukdar; Akarawit Eiamsamarng (Siriraj Medical Journal)
Objective: Postoperative visual loss resulting from posterior ischemic optic neuropathy (PION) after spinal surgery is rare but devastating. A potential risk factor is the prone position during prolonged spinal surgery. We hypothesized that if this risk factor is linked to PION, the retinal nerve fiber layer (RNFL) and macular ganglion cell-inner plexiform layer (GCIPL) should decrease post-surgery.